Digital Marketing Strategies for Elementary School Image and Competitiveness: A Systematic Review - Abdul Hamid; Salamun Salamun; Maulina Amalia Muslih (Penerbit Goodwood, 2026)
Purpose: This study aims to review digital marketing strategies and their role in shaping school image and strengthening competitiveness in elementary education. Methodology: This study used a qualitative literature review method by analyzing peer-reviewed journals, books, and academic publications obtained through Google Scholar. The selection followed PRISMA-aligned procedures based on relevance, credibility, and publication recency, mainly from 2018 to 2026. Data were analyzed through content analysis, including data reduction, thematic grouping, and interpretive synthesis. Results: The findings show that digital marketing strategies, such as social media management, official website development, content creation, and community engagement, support school image formation and competitive differentiation. Platforms such as Instagram, Facebook, TikTok, and YouTube help schools promote achievements, programs, and institutional culture to broader audiences. Official websites also strengthen credibility, transparency, and accessibility. However, implementation is often limited by low staff digital literacy, weak branding strategies, inadequate technological infrastructure, and inconsistent content management. Conclusions: Digital marketing is an important strategic tool for improving elementary school image and competitiveness in the digital era. Its success depends on integrated planning, relevant content, appropriate platform selection, staff capability, and consistency between digital promotion and actual educational quality. Limitations: This study is limited to literature-based analysis and does not include primary data from schools, parents, or stakeholders. Contribution: This study contributes to digital marketing literature in elementary education and offers practical insights for school managers and policymakers.